Buprenorphine Use for Analgesia in Palliative Care - Leanne K. Jackson; Ivy O. Poon; Mary A. Garcia; Syed Imam; Ursula K. Braun (MDPI AG, 2024)
Buprenorphine is a semi-synthetic long-acting partial µ-opioid receptor (MOR) agonist that can be used for chronic pain as a sublingual tablet, transdermal patch (Butrans®), or a buccal film (Belbuca®). Buprenorphine's unique high receptor binding affinity and slow dissociation at the MOR allow for effective analgesia while offering less adverse effects compared to a full agonist opioid, in particular, less concern for respiratory depression and constipation. It is underused in chronic pain and palliative care due to misconceptions and stigma from its use in opioid use disorder (OUD). This case report discusses the unique pharmacology of buprenorphine, including its advantages, disadvantages, available formulations, drug-drug interactions, initiation and conversion strategies, and identifies ideal populations for use, especially within the palliative care patient population.